The Poetics of Murder in Popular Slovenian Crime Fiction from the Perspectives of Criminological Theories - Mlačnik, Primož (Slavia Centralis, 2023)
The article draws on criminological theories and seeks to discover what different interpretations of the origins of crime can tell us about Slovenian crime fiction. The article introduces the basic characteristics of classical, positivist, interactionist and conflict criminological explanations of crime. This is folowed by the analysis of the poetics of murder in popular Slovenian crime fiction by Avgust Demšar and Tadej Golob from the perspectives of criminological theories. We find that standard continuous features appear in the crime fiction of both writers. Classical and positivist poetics of murder predominate, attributing the causes of crime to human opportunism and the individual’s pathological nature, respectively. The discussed crime novels are also characterised by the narrative red herring, or the semantic gap derived from deceiving detective clues, between the novelistic discourse of crime and the discourse of crime derived from the poetics of individual murders.